East Africa Community (EAC) non-tariff barriers and their effects on Tanzanian small and medium agro enterprises cross border trade - Mkuna, Eliaza (Sokoine University of Agriculture, 2024)
A dissertation submitted as a partial fulfillment for the requirement of the award of Master’s of Science Degree in Agricultural and Applied Economics (MSc. in Agricultural and Applied Economics) of Sokoine University of Agriculture.